Observation of chiral Landau levels in two-dimensional acoustic system - Yixian Liu; Kaichong Li; Wenjie Liu; Zhiwang Zhang; Ying Cheng; Xiaojun Liu (Quantum Frontiers)
Abstract Landau levels, previously proposed and verified in condensed matter systems, are conventionally achieved by introducing an external magnetic field that interacts with electrons. In phononic systems, people have proposed the method of applying strain to structures to form artificial synthetic magnetic fields, which in turn induces the emergence of Landau levels. While most of the current implementations about Landau levels are based on three-dimensional (3D) Weyl systems, the experimental realization of chiral Landau levels in two-dimensional (2D) Dirac acoustic systems remains an open and interesting topic. In this work, we present an innovative approach to generate the chiral Landau levels within a 2D acoustic system by introducing an in-plane artificial pseudomagnetic field. Through breaking the spatial parity symmetry and opening the Dirac cones, we introduce position-dependent effective mass terms to Hamiltonian and confirm the existence of chiral Landau levels by simulations and experiments. Furthermore, We verify the strong robustness of the zeroth Landau level to different kinds of defects. This work provides a feasible way to realize chiral Landau levels in 2D acoustic systems and suggests potential applications in other 2D artificial structures.